2017
DOI: 10.5455/ijlr.20170605023751
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Lead and Cadmium Status and its Effect on Biochemical Profile of Cattle Reared Around Industrial Effluent Contaminated Area

Abstract: Study was conducted to assess lead (Pb) and cadmium (Cd)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
2
0
0
Order By: Relevance
“…The significant increase of AST, ALT activity and decreased albumin is in agreement to those results. In hepatocellular liver diseases due to defective albumin synthesis there may be hypoalbuminemia (Chand et al, 2017). Increased ALP and GGT activity observed in the buffaloes naturally exposed to arsenic contamination might be due to hepatic dysfunction (Dash et al, 2016) which is in concurrence with the present study.…”
Section: Pearson's Correlation Between Plasma Enzymes Profile and Blo...supporting
confidence: 90%
See 1 more Smart Citation
“…The significant increase of AST, ALT activity and decreased albumin is in agreement to those results. In hepatocellular liver diseases due to defective albumin synthesis there may be hypoalbuminemia (Chand et al, 2017). Increased ALP and GGT activity observed in the buffaloes naturally exposed to arsenic contamination might be due to hepatic dysfunction (Dash et al, 2016) which is in concurrence with the present study.…”
Section: Pearson's Correlation Between Plasma Enzymes Profile and Blo...supporting
confidence: 90%
“…In the present study, significantly higher levels of AST, ALP activities and reduced plasma levels of total protein and albumin clearly suggest the hepatic dysfunction in cattle with higher blood metal levels. Chand et al, (2017) observed the same result in biochemical profile in cattle around industrial effluent contaminated area of kali river of Meerut city. Lead induced hepatic dysfunction in cattle was revealed by the elevated activities of AST, ALP as biomarker for liver functions and synthesis of albumin largely depends on the liver function status (Flora et al, 2012).…”
Section: Pearson's Correlation Between Plasma Enzymes Profile and Blo...supporting
confidence: 68%